2010
DOI: 10.4161/viru.1.5.13110
|View full text |Cite
|
Sign up to set email alerts
|

Successful, combined long-term treatment of cerebral aspergillosis in a liver transplant patient

Abstract: Invasive aspergillosis has long been recognized as one of the most significant and often fatal opportunistic fungal infections in liver transplant recipients. We report a case of a liver transplant recipient who developed an Aspergillus fumigatus brain abscess that produced significant neurologic symptoms. The patient was managed successfully with a combination of surgery and medical treatment with Voriconazole. To our knowledge, this is the second such case reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…These findings are consistent with reported evidence of clinical efficacy for voriconazole in Aspergillus infections of the CNS (7). Multiple case reports have been published documenting successful treatment of rhinocerebral aspergillosis (14), cerebellar abscesses (15), cerebral aspergillosis associated with liver transplant (16), and sellar Aspergillus abscesses (17). A retrospective analysis of 81 cases of aspergillosis of the CNS treated with voriconazole indicated that voriconazole treatment combined with neurosurgery is the most effective treatment for this type of infection (5).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with reported evidence of clinical efficacy for voriconazole in Aspergillus infections of the CNS (7). Multiple case reports have been published documenting successful treatment of rhinocerebral aspergillosis (14), cerebellar abscesses (15), cerebral aspergillosis associated with liver transplant (16), and sellar Aspergillus abscesses (17). A retrospective analysis of 81 cases of aspergillosis of the CNS treated with voriconazole indicated that voriconazole treatment combined with neurosurgery is the most effective treatment for this type of infection (5).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In a few case reports and a retrospective study, immediate neurosurgical intervention for diagnosis and therapy also is associated with improved outcomes. 5,7,22 In our case, immediate neurosurgical intervention (excisional biopsy) for diagnosis, reduction of immunosuppression, and antifungal treatment with vorico-nazole resulted in successful outcome.…”
Section: Discussionmentioning
confidence: 66%
“…However, invasive aspergillosis is one of the most important and often fatal opportunistic fungal infections, with an associated mortality rate > 90%, especially when the central nervous system is affected in liver transplant recipients. [1][2][3][4][5] Aspergillus infections usually occur within the first month after transplant, and the most frequent form of invasive aspergillosis is pulmonary aspergillosis. However, 10% to 25% of all cases of invasive aspergillosis have central nervous system involvement, presumably disseminated through the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…Voriconazole, which can penetrate effectively into the CSF and brain tissue, was proved to be superior to amphotericin B in terms of the response rate, the survival rate and safety [11]. In recent years, multiple case reports revealed that neurosurgical interventions and combination antifungal therapies might improve the outcome in CA [12,13]. The standard strategy and drug formulations need to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 97%